The Implementation of Nature-Based Learning to Foster Creativity and Independence in Early Childhood - Permatasari, Gadis; Putri, Eka; Lailatul, Ariesca; Andriani, Dhini; Putri Yuniar, Dias (Nak-Kanak: Journal of Child Research, 2025)
Background of the study: Early childhood is a crucial stage of rapid development across cognitive, motor, social, and emotional domains. To support this growth, learning approaches that foster creativity and independence are essential. Nature-based learning provides opportunities for children to interact directly with their environment, offering rich multisensory experiences that stimulate imagination, creativity, and problem-solving. Through exploration and hands-on engagement with nature, children also develop autonomy, responsibility, and risk assessment skills. This study explores the role of nature-based learning in fostering creativity and independence in the context of Early Childhood Education (ECE) in Indonesia. Aims and scope of paper: This paper examines how nature-based learning can enhance creativity and independence in children aged 0–6 years. It discusses key theories, principles, and benefits, provides practical applications from ECE settings, and highlights the role of educators in designing effective nature-based learning experiences. Methods: A literature review approach was used, drawing from academic journals, books, and relevant articles. The data were analyzed qualitatively to identify concepts, benefits, and teaching strategies related to nature-based learning in early childhood. Results: The findings suggest that nature-based learning significantly supports the development of creativity and independence. Activities like outdoor play, exploration, and gardening enhance children's ability to express ideas and solve problems, while also fostering decision-making and self-regulation. Educators play a vital role as facilitators in creating safe, engaging environments that promote meaningful exploration. Contribution: This study offers practical guidance for ECE educators and contributes to the academic discussion on holistic, contextual learning models that support young children's development.